Estimation of inventory for deteriorating items with non-linear demand considering discount and without discount policy (Journal of Naval Architecture and Marine Engineering, 2016)
This paper develops an inventory model for deteriorating items consisting the ordering cost, unit cost, opportunity cost, deterioration cost and shortage cost. In this inventory model instead of linear demand function nonlinear exponential function of time for deteriorating items with deterioration rate has been considered. The effects of inflation and cash flow are also taken into account under a trade-credit policy of discount and without discount with time. In order to validate the model, numerical examples have been solved by bisection method deploying Matlab.  Further, in order to estimate the cash flow the sensitivity of different parameters is considered.